2019
DOI: 10.1021/acssuschemeng.9b01012
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Natural Products from Deep Eutectic Solvents by Mimicking Denaturation

Abstract: A strategy was developed to recover natural products from deep eutectic solvents based on denaturation of the solvents. A method similar to nucleic acid denaturation was used to disrupt the intermolecular forces in the deep eutectic solvents to reduce their ability to solubilize and interact with the flavonoids at recovery. MIL-100 (Cr) was added to the system for sorptive separation and recovery of the target compounds from the denaturized deep eutectic solvents. The factors affecting denaturation of the deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…In their study, several macroporous resins were tested (NKA-9, AB-8 and D101) for the recovery of flavonoids from the DES crude extract and the resin AB-8 was confirmed as the most promising with an excellent recovery power (more than 72% of the total extract content). In this study a 95% ethanol (v:v) was used as elution solvent, and certainly this stage of the method is more environmentally friendly than the methanol elution described above [165]. The authors also evaluated the possibility of DES recycling and found that the same solvent can be used four times, at least, with a promising result compared to the first extraction cycle (more than 75%).…”
Section: Recovering Of the Bioactive Compounds From The Des/nades Extmentioning
confidence: 99%
See 3 more Smart Citations
“…In their study, several macroporous resins were tested (NKA-9, AB-8 and D101) for the recovery of flavonoids from the DES crude extract and the resin AB-8 was confirmed as the most promising with an excellent recovery power (more than 72% of the total extract content). In this study a 95% ethanol (v:v) was used as elution solvent, and certainly this stage of the method is more environmentally friendly than the methanol elution described above [165]. The authors also evaluated the possibility of DES recycling and found that the same solvent can be used four times, at least, with a promising result compared to the first extraction cycle (more than 75%).…”
Section: Recovering Of the Bioactive Compounds From The Des/nades Extmentioning
confidence: 99%
“…For the recovery of the extracted bioactive compounds, in particular the flavonoids, there are several approaches such as solid phase extraction (SPE) [47,164], macroporous resin adsorption [79,103,111,143,144,148], anti-solvent precipitation [107,164,165], back-extraction [122], and adsorption chromatography [166] that have been evaluated to date.…”
Section: Recovering Of the Bioactive Compounds From The Des/nades Extmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a novel method for extracting the flavonoids from the DES involves the mimicking of DNA denaturation in the DES, as described by Tian et al [56]. According to their research, the main goal in removing the flavonoids from the DES is the breakdown of the hydrogen mesh that holds the DES together, which is a process similar to denaturation.…”
Section: Separation Techniquesmentioning
confidence: 99%